PENGEMBANGAN MEDIA PEMBELAJARAN BILANGAN CACAH BERBASIS ANDORID UNTUK SISWA SD/MI DENGAN METODE ADAPTIVE SOFTWARE DEVELOPMENT - prabowo, mei; Syafiq, Mohd (LP2M Universitas Nurdin Hamzah, 2024)
Development of Andorid-Based Learning Media on Whole Numbers for Elementary/MI Students Using the Adaptive Software Development Method, The purpose of this study is to develop an Android-based whole number learning media application for SD/MI using the Adaptive Software Development method. The development of this application is divided into 2 iterations. Functional testing method using black-box testing technique. From the results of black-box testing, it show that all features/functions run well and smoothly. The usability method is used to see user ratings of this learning media application. There are 3 aspects which are Learnability, Flexibility, and Effectiveness. The overall value of the usability test results is 78.82%. Based on the eligibility category, the value is included in the feasible category. So that this android-based whole number learning media application is feasible to implement.